Notes on the phenology of dragonflies and damselflies (Insecta: Odonata) in the Aras River Valley of Turkey - Denis Kitel; Kyle Kittelberger; Kayahan Ağirkaya; Gul Tutar; Çağan H. Șekercioğlu (Caucasiana)
A check-list of Odonata found at Aras River Valley in Kars and Iğdır provinces of Turkey is published for the first time, representing 38 species. The abundance of species from March to November is noted by month, with the phenology of the flight period indicated. Summer months unsurprisingly host the highest number of species, up to 28 in June. We provide a complete phenology for the imago (adult) presence in the area for 22 species, from their emergence to their disappearance at the end of their flight period and life cycle. Short notes regarding selected species which are either rare in the region or have international protection status are also provided. This study shows that the Aras River Valley is an important place for Odonata, especially Onychogomphus flexuosus and Libellula pontica, species which are classified as “Vulnerable” and “Near Threatened”, respectively, in the present IUCN Red List of threatened species.